Improvement of well drainage radius calculation - Lubkov, Michail; Zakharchuk, Oksana (Academic journal Industrial Machine Building Civil Engineering, 2022)
The calculation of well drainage radius is improved on the example of Chervonozayarske gas field. Theoretical research methods are applied, which include a systematic analysis of the information used, numerical modeling based on the combined finite element-difference method, methods of visual representation of the information obtained, analytical methods To increase the accuracy of the calculation of the well drainage radius, the heterogeneity of the porous medium structure was taken into account. It is established that the drainage radius of a gas well expands with time. This allows to determine the optimal grid of production wells, the number and location of injection wells to ensure their interaction, and hence ¬ reduce material costs in the gas industry